Genetic Elimination of Connective Tissue Growth Factor in the Forebrain Affects Subplate Neurons in the Cortex and Oligodendrocytes in the Underlying White Matter - I-Shing Yu; Ho-Ching Chang; Ko-Chien Chen; Yi-Ling Lu; Horng-Tzer Shy; Chwen-Yu Chen; Kuang-Yung Lee; Kuang-Yung Lee; Li-Jen Lee; Li-Jen Lee; Li-Jen Lee (Frontiers Media S.A., 2019)
Connective tissue growth factor (CTGF) is a secreted extracellular matrix-associated protein, which play a role in regulating various cellular functions. Although the expression of CTGF has been reported in the cortical subplate, its function is still not clear. Thus, to explore the significance of CTGF in the brain, we created a forebrain-specific Ctgf knockout (FbCtgf KO) mouse model. By crossing Ctgffl/fl mice with Emx1-Cre transgenic mice, in which the expression of Cre is prenatally initiated, the full length Ctgf is removed in the forebrain structures. In young adult (2-3 months old) FbCtgf KO mice, subplate markers such as Nurr1 and Cplx3 are still expressed in the cortical layer VIb; however, the density of the subplate neurons is increased. Interestingly, in these mutants, we found a reduced structural complexity in the subplate neurons. The distribution patterns of neurons and glial cells, examined by immunohistochemistry, are comparable between genotypes in the somatosensory cortex. However, increased densities of mature oligodendrocytes, but not immature ones, were noticed in the external capsule underneath the cortical layer VIb in young adult FbCtgf KO mice. The features of myelinated axons in the external capsule were then examined using electron microscopy. Unexpectedly, the thickness of the myelin sheath was reduced in middle-aged (>12 months old), but not young adult FbCtgf KO mice. Our results suggest a secretory function of the subplate neurons, through the release of CTGF, which regulates the density and dendritic branching of subplate neurons as well as the maturation and function of nearby oligodendrocytes in the white matter.